1998
DOI: 10.1210/endo.139.3.5775
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Dependent Regulation of Retinoic Acid Receptor α in Rat Testis: In Vivo Response to Depletion and Repletion of Vitamin A

Abstract: Male animals are sterile due to testicular degeneration in the absence of retinoic acid (RA) or functional retinoic acid receptor-alpha (RAR alpha). This degeneration can be reversed by injecting retinol, a precursor of RA, into vitamin A-deficient (VAD) rats. To determine the relationship between this ligand-dependent testicular degeneration and regeneration and the expression levels of RAR alpha messenger RNA and protein, testes were depleted and then replenished with retinol in vivo. Results showed that RAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…In this report, we demonstrate that the ligand, tRA, increases the nuclear translocalization of RAR␣ within 30 min in mouse Sertoli cell lines (MSC-1 and MSC-1F) and that this localization is independent of new protein synthesis. This regulation of nuclear localization by ligand is consistent with the previous finding in the vitamin A-deficient rat model in which the RAR␣ subcellular localization in germ cells changed from primarily nuclear to more cytoplasmic following retinol depletion (33). These results clearly demonstrate the importance of ligand in the regulation of RAR␣ receptor subcellular localization.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this report, we demonstrate that the ligand, tRA, increases the nuclear translocalization of RAR␣ within 30 min in mouse Sertoli cell lines (MSC-1 and MSC-1F) and that this localization is independent of new protein synthesis. This regulation of nuclear localization by ligand is consistent with the previous finding in the vitamin A-deficient rat model in which the RAR␣ subcellular localization in germ cells changed from primarily nuclear to more cytoplasmic following retinol depletion (33). These results clearly demonstrate the importance of ligand in the regulation of RAR␣ receptor subcellular localization.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, RAR␣ expression is induced in a time-dependent manner by tRA treatment, increasing significantly by 1 h, reaching a maximum of 2.5-fold within 3 h, and then declining by 24 h. This increase requires new protein synthesis and is probably due to the RAR␣ serving as an endogenous RARE-containing reporter gene because an RARE has previously been located within the promoter region of RAR␣ 2 (32). The pattern of increase in the expression of RAR␣ protein by tRA treatment in mouse Sertoli cell lines parallels the retinol-induced effect on RAR␣ protein expression previously observed in vivo in the testis of vitamin A-deficient rats (33). Following an injection of retinol into a vitamin A-deficient rat, the RAR␣ protein level reached a maximum level at 4 h and then decreased to a basal level within 24 h. At the mRNA level, there was nearly a 3-fold increase of RAR␣ mRNA as early as 2 h post-injection of retinol, followed by a subsequent decrease by 12 h (33).…”
Section: Discussionsupporting
confidence: 64%
“…However, some studies have demonstrated that RAR and TR are retained in the cytoplasm and move to the nucleus when ligands are supplied (13)(14)(15)(16). In particular, we also found that RAR␣ shuttles between the cytoplasm and the nucleus in the Sertoli cell line TM4 in response to AtRA (Fig.…”
Section: Resultssupporting
confidence: 51%
“…Cells-It has been reported that apoRAR␣ is cytoplasmic and holo-RAR␣ is nuclear in mouse testis Sertoli cell lines (15,16). These findings led us to investigate the role of CART1 in the intracellular distribution of RAR␣ in Sertoli cells.…”
Section: Cytoplasmic Distribution Of Endogenous Rar In Testis Sertolimentioning
confidence: 99%
See 1 more Smart Citation